Comparison of Two Preparation Methods on Catalytic Activity and Selectivity of Ru-Mo/HZSM5 for Methane Dehydroaromatization. (2nd July 2014) - Petkovic, Lucia M.; Ginosar, Daniel M.
Abstract : Catalytic performance of Mo/HZSM5 and Ru-Mo/HZSM5 catalysts prepared by vaporization-deposition of molybdenum trioxide and impregnation with ammonium heptamolybdate was analyzed in terms of catalyst activity and selectivity, nitrogen physisorption analyses, temperature-programmed oxidation of carbonaceous residues, and temperature-programmed reduction. Vaporization-deposition rendered the catalyst more selective to ethylene and coke than the catalyst prepared by impregnation. This result was assigned to lower interaction of molybdenum carbide with the zeolite acidic sites.